EVALUATING EFFECTIVENESS OF ENSEMBLE CLASSIFIERS WHEN DETECTING FUZZERS ATTACKS ON THE UNSW-NB15 DATASET - Thanh, Hoang Ngoc; Lang, Tran Van (Journal of Computer Science and Cybernetics, 2020)
The UNSW-NB15 dataset was created by the Australian Cyber Security Centre in 2015 by using the IXIA tool to extract normal behaviors and modern attacks, it includes normal data and 9 types of attacks with 49 features. Previous research results show that the detection of Fuzzers attacks in this dataset gives the lowest classification quality. This paper analyzes and evaluates the performance of using known ensemble techniques such as Bagging, AdaBoost, Stacking, Decorate, Random Forest and Voting to detect FUZZERS attacks on UNSW-NB15 dataset to create models. The experimental results show that the AdaBoost technique with the component classifiers using decision tree for the best classification quality with F-Measure is 96.76% compared to 94.16%, which is the best result obtained by using single classifiers and 96.36% by using the Random Forest technique.